Coating Composition Evolution during the Deposition of Al and N from Plasma on a Cylindrical Substrate; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Shanin S. A. Sergei Aleksandrovich (Discharge and Plasma-Beam Technology, 2016)
Title screen